Evaluasi Kualitas Website Pemerintah Daerah Dengan Menggunakan WebQual 4.0 Pada Instansi Pemerintahan ABC - M Afriansyah; Andi Sunyoto; Asro Nasiri (STMIK Sinar Nusantara, 2020)
The purpose of website quality evaluation is helping ABC Government Institution to determine the significant influence of usability, information quality, and service interaction as a whole and partially. The research examines the relationship of usability, information quality, and service interaction in influencing the quality of the website in accordance with the reference webQual 4.0, by distributing questionnaires data processed using SPSS and analyzed by multiple regression analysis methods. The results of the analysis of all questions in the questionnaire were valid and reliable, the Cronbach alpha value for each statement> 0.1875. The influence of X1 usability, X2 information quality, and X3 service interaction variables on website Y1 quality is 63.8%. The value of Adjusted R Square is 0.407 or 40.7% the influence of independent variables on the dependent variable. In this study, the regression model equation is Y = 0.96 + 0.517X1 + 0.754X2 + 0.760X3. The evaluation of website quality should be done on dimensions or variable usability. Thus, the respondents feel less understanding or have inconvenience in operating the website, and also find some difficult to explore the website.Keywords: Evaluation, WebQual, Regression